2020
DOI: 10.1200/jco.19.03355
|View full text |Cite
|
Sign up to set email alerts
|

ASCEND: Phase III, Randomized Trial of Acalabrutinib Versus Idelalisib Plus Rituximab or Bendamustine Plus Rituximab in Relapsed or Refractory Chronic Lymphocytic Leukemia

Abstract: PURPOSE Acalabrutinib, a highly selective, potent, Bruton tyrosine kinase inhibitor, was evaluated in this global, multicenter, randomized, open-label, phase III study in patients with relapsed/refractory (R/R) chronic lymphocytic leukemia (CLL). METHODS Eligible patients, aged ≥ 18 years with R/R CLL, were randomly assigned 1:1 centrally and stratified by del(17p) status, Eastern Cooperative Oncology Group performance status score, and number of prior lines of therapy. Patients received acalabrutinib monother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
294
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(319 citation statements)
references
References 35 publications
14
294
1
10
Order By: Relevance
“…This is based on a phase III trial in which acalabrutinib was superior to either bendamustine plus rituximab or idelalisib plus rituximab. 131 In this trial, prior ibrutinib therapy was not allowed, but a separate trial has shown that 85% of patients who were intolerant to ibrutinib were subsequently able to take acalabrutinib, with a 76% response rate. 132 Despite all recent therapeutic advances, a proportion of patients will still fail to respond and should be considered for curative therapy.…”
Section: Relapsed/refractory Diseasementioning
confidence: 99%
“…This is based on a phase III trial in which acalabrutinib was superior to either bendamustine plus rituximab or idelalisib plus rituximab. 131 In this trial, prior ibrutinib therapy was not allowed, but a separate trial has shown that 85% of patients who were intolerant to ibrutinib were subsequently able to take acalabrutinib, with a 76% response rate. 132 Despite all recent therapeutic advances, a proportion of patients will still fail to respond and should be considered for curative therapy.…”
Section: Relapsed/refractory Diseasementioning
confidence: 99%
“…These drugs have improved response rates, progression-free survival (PFS), and overall survival (OS), including in patients with high-risk disease. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] AlloHCT carries risks including graft-versushost disease (GVHD), organ toxicity, and nonrelapse mortality (NRM); in light of the potential for long-term disease control with sequential administration of NAs, the necessity of pursuing longterm disease control with alloHCT is less defined. 25 Despite effective NAs, drug intolerance, progression, primary resistance, and high-grade transformation remain as serious limitations for many patients.…”
Section: Introductionmentioning
confidence: 99%
“…ELEVATE-TN reported that acalabrutinib alone or acalabrutinib-chlorambucil is superior to obinutuzumabobinutuzumab [81]. ASCEND reported that acalabrutinib improved PFS compared with idelalisib-rituximab or BR [82]. Several phase III clinical trials of acalabrutinib in CLL/SLL are ongoing, including ELEVATE-RR, which compares acalabrutinib to ibrutinib, and ACE-CL-311, which compares acalabrutinib-venetoclax with/without obinutuzumab versus chemoimmunotherapy.…”
Section: Clinical Development Of Btk Inhibitors In Cll/sllmentioning
confidence: 99%